2023
DOI: 10.3390/microorganisms11061618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Enterotoxins and Antimicrobial Resistance in Microorganisms Isolated from Raw Sheep Milk and Cheese: Ensuring the Microbiological Safety of These Products in Southern Brazil

Creciana M. Endres,
Eliana Moreira,
Andressa B. de Freitas
et al.

Abstract: This study emphasizes the importance of monitoring the microbiological quality of animal products, such as raw sheep’s milk and cheese, to ensure food safety. In Brazil, there is currently no legislation governing the quality of sheep’s milk and its derivatives. Therefore, this study aimed to evaluate: (i) the hygienic-sanitary quality of raw sheep’s milk and cheese produced in southern Brazil; (ii) the presence of enterotoxins and Staphylococcus spp. in these products; and (iii) the susceptibility of the isol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Ashraf et al detected the presence of the AAC ( 6 ′) -APH ( 2 ″) gene complex in raw milk and dairy product samples [ 49 ], which was also detected by Liu et al in various animal-origin raw milk samples [ 50 ]. Endre et al demonstrated the presence of the AAC ( 6 ′) gene in raw sheep milk and cheese samples [ 51 ]. Parry-Hanson Kunadu et al detected the AAC ( 6 ′) -Iy gene in raw cheese [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ashraf et al detected the presence of the AAC ( 6 ′) -APH ( 2 ″) gene complex in raw milk and dairy product samples [ 49 ], which was also detected by Liu et al in various animal-origin raw milk samples [ 50 ]. Endre et al demonstrated the presence of the AAC ( 6 ′) gene in raw sheep milk and cheese samples [ 51 ]. Parry-Hanson Kunadu et al detected the AAC ( 6 ′) -Iy gene in raw cheese [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different CNS species have been identified as part of the dominant and subdominant microflora of many kinds of traditional cheeses [33,34] (Table 1). M. sciuri, despite being mainly associated with the ripening of fermented meat products such as cured meats and sausages [95,96,121], has also been found in French smear cheeses [33], German cheeses [34], Brazilian cheeses [35], and the traditional Middle East Surk cheese [36] (Table 1).…”
Section: Mammalicoccus Sciuri (Formerly Known As Staphylococcus Sciuri)mentioning
confidence: 99%